Android-Based Digitalization of Fresh Fruit Bunch Harvest and Supply Chain with Geo-Tagging and Online-Offline Cloud Synchronization - Ifan Gultom; Ratu Mutiara Siregar; Andi Prayogi (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
Background: Manual recording of Fresh Fruit Bunch (FFB) harvest activities at Kebun Tanah Putih PTPN IV Regional 3 results in reporting delays of up to 24 hours, a human error rate of approximately 15–20% per entry, inability to verify harvest locations spatially, and absence of real-time monitoring under limited network connectivity. Objective: This study develops HarvestTrack, an Android and web-based mobile information system for FFB harvest recording and supply chain monitoring, aimed at improving data accuracy, operational efficiency, and transparency in oil palm plantation management. Method: A Research and Development (R&D) methodology with a prototyping approach was employed, covering requirements analysis, system design, implementation, and testing. The system was built with Flutter, Firebase Firestore (cloud backend), and SQLite (local storage) using an offline-first architecture. Delta synchronization via WorkManager and geo-tagging via Fused Location Provider API (≤10 m accuracy) were implemented. Testing included functional, performance, and User Acceptance Testing (UAT). Results: Functional testing confirmed 100% success for offline data recording and automatic cloud synchronization (<5 seconds/entry). Geo-tagging achieved ≤10 m accuracy in 95% of 40 field test locations. Last-Write-Wins (LWW) conflict resolution attained an error rate below 2%. Three role-based user modules (KCS, Foreman, Admin) were fully implemented with differentiated access controls. Contribution: HarvestTrack is the first integrated system combining offline-first architecture, real-time geo-tagging, automated conflict handling, and web-based monitoring dashboard for FFB supply chain digitalization in Indonesia's oil palm sector.